the academic leaders role in Jordanian universities in the use of technology at various levels of management - Al-Omari, Bassam; Mourtada, Mariam abdullha (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
This study aimed to discover the academic leaders role in Jordanian universities in the use of technology at various levels of management, the researcher used the descriptive analytical approach among a questionnaire prepared for this purpose and distributed to a sample consisting of (399) respondents, and to achieve the study of its goals, raised the following main question What is the academic leaders role in Jordanian universities in the use of technology at various administrative levels, and the study reached a number of results, the most prominent of which are: The role of academic leaders in Jordanian universities in the use of technology came in a medium degree, and there are no differences Statistically significant at the level of significance (α = 0.05) in the level of the role of academic leaders in activating the use of technology in university administration due to gender and experience variables, and academic rank. هدفت هذه الدراسة إلى الكشف دور القيادات الأكاديمية في الجامعات الأردنية في استخدام التكنولوجيا في مختلف المستويات الإدارية، استخدم الباحثان المنهج الوصفي التحليلي من خلال استبانة تم إعدادها لهذا الغرض ووزعت على عينة مكونة من (399) مستجيباً، ولتحقيق الدراسة لأهدافها، فقد طرحت السؤال الرئيس الآتي: ما دور القيادات الأكاديمية في الجامعات الأردنية في استخدام التكنولوجيا في مختلف المستويات الإدارية، وتوصلت الدراسة لعدد من النتائج من أبرزها: أن دور القيادات الأكاديمية في الجامعات الأردنية في استخدام التكنولوجيا جاءت بدرجة متوسطة، وعدم وجود فروق ذات دلالة إحصائية عند مستوى الدلالة (α=0.05) في مستوى دور القيادات الأكاديمية في تفعيل استخدام التكنولوجيا في الإدارة الجامعية تعزى لمتغيرات الجنس والخبرة، والرتبة الأكاديمية.